Association of OAS1 and MxA variants with COVID-19 in Pakistani patients - Shaikh, Naila; Khidri, Feriha Fatima; Shaikh, Hina; Mahmood, Amber; Hayat, Atif Sitwat; Waryah, Yar Muhammad; Devrajani, Tarachand; Ujjan, Ikram Din; Waryah, Ali Muhammad (The Journal of Infection in Developing Countries, 2024)
Introduction: Coronaviruses, a family of enveloped RNA viruses, have been implicated in various clinical disorders including coronavirus disease 2019 (COVID-19). Host genetic factors, including the OAS1 and MxA gene variants may have a role in determining susceptibility to viral infections. Understanding the genetic factors involved in unraveling COVID-19`s diverse clinical outcomes is critical for disease management. This study investigated the impact of OAS1 rs2660 and MxA rs2071430 genotypes on COVID-19 susceptibility and severity among Pakistani patients. Methodology: This was a comparative cross-sectional study. Fifty patients diagnosed with COVID-19 and 50 controls were recruited and genotyped for the selected gene variants. Results: The OAS1 gene rs2660 exhibited an association with COVID-19 susceptibility in various genetic models. The risk decreased with AG genotype (OR = 0.23, 95% CI = 0.09-0.58; p = 0.0011) compared to GG in codominant models. In dominant (OR = 0.35, 95% CI = 0.15-0.81; p = 0.013) and overdominant (OR = 0.21, 95% CI = 0.08-0.53; p = 0.0005) models, the single nucleotide variant (SNV) decreased COVID-19 susceptibility risk. There was no association of OAS1 rs2660 genotypes with COVID-19 severity. We did not find a significant association between MxA rs2071430 variant and COVID-19 susceptibility. Conclusions: OAS1 rs2660 AG genotype showed decreased risk of COVID-19 susceptibility among Pakistani patients. This study provides insight into the role of the OAS1 and MxA variants in COVID-19. This finding could aid researchers in understanding genetic susceptibility and severity in COVID-19 by identifying at-risk individuals and determining the optimal treatment.